Age estimation using the maxillary canine pulp/tooth ratio in Korean adults: A CBCT buccolingual and horizontal section image analysis. (June 2017) - Lee, Seung-Min; Oh, Sewoong; Kim, Jinmi; Kim, You-Min; Choi, Youn-Kyung; Kwak, Hyun Ho; Kim, Yong-Il
Abstract: Various age estimation approaches have been proposed in dental clinic, and it is necessary to have a simple, easy, fast and conservative method that can be applied to living individuals. In this study, an age estimation model was established by measuring the change in the pulp/tooth ratio that occurs due to the progression of pulp calcification associated with aging. This was done using CBCT to image the buccolingual and horizontal dimensions of the maxillary canine. Two hundred and five clinical CBCT images (age range: 20–77 years) were analyzed. In this study, we used the largest pulp/tooth area (S, sagittal pulp/tooth area ratio %) on the buccolingual sectional image in order to overcome the limitations of using a superimposed image in 2D. In addition, horizontal section images were obtained from the CEJ(HC, horizontal pulp/tooth area ratio % on CEJ) and 1/2 of root length(HA, horizontal pulp/tooth area ratio % on mid-root) positions, where the greatest degree of calcification takes place. The pulp/root area ratios were calculated from these images using a numerical analysis software. According to the resultant age estimation model, age can be. This method uses the largest buccolingual and horizontal sectional CBCT canine images without image distortion. Bucolingual sectional image(S) is the largest predictor variables(36.4%) compared to HC(29.7%) and HA(22.4%). This model involves the use of a numerical analysis software, which is quick and easy to use, because it calculate pulp and tooth area by semi-automatic. Highlights: The canine has the largest pulp and tooth area in 3D CBCT buccolingual sectional images. Buccolingual sections on CBCT images show no interference from neighboring teeth. The pulp/tooth ratio of the buccolingual section had a higher correlation with age. ANCOVA results showed a significant difference in HA (p<0.05) between sexes.